Cultural Accounting Of Ajikrame Sorong Serah Value Determination: An Ethnographic Approach - Nauva Safitri; Novia Rizki (International Environmental Conferrence on Biosustainability Advancement, 2025)
Sorong Serah is a Lombok tradition that is still preserved through the cultural practice of elopement. This research aims to understand the accounting practices in Sorong Serah customary wedding expenses, especially the determination of ajikrame. The approach used in this research is qualitative and based on ethnographic methods. The results of this study found that the factors determining the cost of Ajikrame, which is one of the main components of the Sorong Serah fee, are education, occupation, family background, and the reference price of Sorong Serah circulating in each region as the basis for determining the Sorong Serah fee. These factors cause the costs that must be incurred by the male party to be higher or the price set by the female party to be more expensive. This is something that is generally accepted and has become a tradition of the Sasak tribe.